A Role for Endogenous Brain States in Organizational Research: Moving Toward a Dynamic View of Cognitive Processes. (January 2019) - Braeutigam, Sven; Lee, Nick; Senior, Carl
The dominant view in neuroscience, including functional neuroimaging, is that the brain is an essentially reactive system, in which some sensory input causes some neural activity, which in turn results in some important response such as a motor activity or some hypothesized higher-level cognitive or affective process. This view has driven the rise of neuroscience methods in management and organizational research. However, the reactive view offers at best a partial understanding of how living organisms function in the real world. In fact, like any neural system, the human brain exhibits a constant ongoing activity. This intrinsic brain activity is produced internally, not in response to some environmental stimulus, and is thus termed endogenous brain activity (EBA). In the present article we introduce EBA to organizational research conceptually, explain its measurement, and go on to show that including EBA in management and organizational theory and empirical research has the potential to revolutionize how we think about human choice and behavior in organizations.